Concept Paper on Communication in Social Media in the Nursing Profession (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2020)
Advances in technology have transformed the way we live, how we work, and how we interact. The use of social media and other electronic communication is expanding exponentially as the number of social media outlets, platforms, and applications available continues to increase. Inappropriate use of social media in various professions causes concerns for employers, educators, and regulators. However, Social media offers nursing many opportunities to allow advancement in the profession. Thus, the objective of the paper is to clarify the meaning of communication on social media in the nursing profession. Findings showed that the wide use of social media outside and inside the healthcare community and the nursing community has far-reaching implications on the nursing profession. Social media enhance access to information by health members and members of the community. Also, individuals, nurses, and professional institutions are embracing social media and recognizing professional, ethical, regulatory, and legal issues with caution. Considering the growing use of social media in the nursing profession with the potential for both benefit and harm, nurses need to draw on available guidance as necessary in the use of social media. As a powerful tool for communication in the nursing profession, nurses utilize social media to communicate effectively within their environment.
Keywords: communication, social media, nursing